2007
DOI: 10.1158/1055-9965.epi-07-0143
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Physical Activity, and Risk of Multiple Myeloma

Abstract: Several studies have reported a positive relation of baseline body mass index (BMI) with multiple myeloma, but data on other correlates of energy balance are limited. We undertook the present analyses to further examine the role of energy balance in multiple myeloma etiology in two large prospective cohorts with biennially updated exposure data. We followed members of the Nurses' Health Study and Health Professionals Follow-up Study cohorts from baseline until multiple myeloma diagnosis, death, or 2002. Adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 36 publications
6
48
0
Order By: Relevance
“…31,32 However, adiponectin is inversely correlated with obesity, and there is increasing evidence to suggest an association between obesity, MGUS, and myeloma. 33,34 Interestingly, in the present study, all samples were age-, sex-, and BMI-matched; therefore, it is unlikely that the differences observed in adiponectin concentrations are simply a reflection of changes in obesity. Furthermore, we have confirmed that differences in glucose, testosterone, or the presence of a metabolic syndrome were not associated with progression from MGUS to myeloma.…”
Section: Discussionmentioning
confidence: 65%
“…31,32 However, adiponectin is inversely correlated with obesity, and there is increasing evidence to suggest an association between obesity, MGUS, and myeloma. 33,34 Interestingly, in the present study, all samples were age-, sex-, and BMI-matched; therefore, it is unlikely that the differences observed in adiponectin concentrations are simply a reflection of changes in obesity. Furthermore, we have confirmed that differences in glucose, testosterone, or the presence of a metabolic syndrome were not associated with progression from MGUS to myeloma.…”
Section: Discussionmentioning
confidence: 65%
“…With insufficient statistical power to jointly examine interactions of follow-up interval and BMI with biomarker concentration in relation to multiple myeloma risk, the present analysis is inconclusive as to whether dysregulation of IGF-1, insulin, or IL-6 explains the association of obesity with multiple myeloma. 5,6 Lastly, the median follow-up interval for study participants was Ͻ 7 years. Although we did not observe biomarker associations with multiple myeloma risk Ͼ 6 years after blood collection, the present analysis could not evaluate whether IGF-1, insulin, or IL-6 dysregulation has an early role in multiple myeloma etiology.…”
Section: Igf-1 Insulin and Il-6 Markers And Myeloma Risk 4935mentioning
confidence: 99%
“…Table 1 presents the main characteristics and results of the 15 cohort studies (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and eight case-control studies (18)(19)(20)(21)(22)(23)(24)(25) included. Three studies investigated more than one physical activity domain (19,24,40) and nine studies provided results stratified by gender (20,22,23,25,26,29,32,39,40).…”
Section: Resultsmentioning
confidence: 99%